Gender, age, academic level and department as correlates of students' perceptions of social networking as learning tool (2013)
Technology, over the ages is recognised as a tool for doing things in neater, faster, better and particularly easier ways. People use technology to make their operations more fascinating, interesting and motivating in all facets of human endeavour including education. The study examined the contributions of age, gender, level of study, and department as correlates of Distance learning students' perceptions of social networking technology as a collaborative learning tool. A validated 4-likert scale questionnaire on students' perception was administered to 360 participants selected through stratified sampling technique. The results of this study showed that gender, field of study, academic level and age group have significant influence on student's perceptions of social networking as a collaborative learning tool. It was recommended that both students and teachers intending to integrate social networking to enrich instructions delivery should be adequately trained and motivated to acquire needed skills and confidence.